Delegated affairs of state administration in the area of Environmental Protection - Lončar, Zoran (Zbornik radova Pravnog fakulteta u Novom Sadu, 2015)
In legal system of the Republic of Serbia there are numerous affairs of the state administration in the field of environmental protection which are, as delegated affairs, performed by the authorities of the provincial and local governments. In addition to inspection control, as the most common type of delegated affair of the state administration, there are many other jobs in different areas of environmental protection, which are by numerous material laws conferred on the administration of the Autonomous Province of Vojvodina or municipalities and cities, and local governments. It an be sad that legal regime of delegated affairs today is well established, but if we intend to ensure quality performance of all delegated activities, normative entrustment should be followed by appropriate transfer of funds in the budget of the autonomous province or local self-government, necessary for their quality performance.